Islamic Education as a Strengthening of Aqidah and Akhlaq in The Society 5.0 Era - Kasman, Adi; Ikhwan, M.; Aziz, Darlis (IAIN Ponorogo, 2022)
With the rapid times, Islamic education faces many challenges. The industrial era 4.0 and society 5.0 has shifted the development of world civilization. This research investigates the challenges of a shifting era for Islamic education. It includes aqidah and akhlaq, which must be prepared to enter the new era. These two things are guidelines that need to be prepared, especially for children as a generational advocates to fortify themselves from the currents of globalization that are not following the teachings of Islam. This research employed qualitative research with a normative approach. It used secondary sources such as books, journals, newspapers, and other documents. Those were valid. Data analysis used descriptive analysis to draw conclusions. This study found that Islamic education can adapt to the new era of society 5.0 by prioritizing critical and innovative thinking. Next, Islamic education must ensure the availability of reliable and competent human resources to strengthen the aqidah and morals of students, especially teachers and education staff. Pendidikan Islam dihadapkan pada tantangan perubahan zaman yang sangat cepat, belum usai bergulirnya era industri 4.0, perkembangan peradaban dunia sudah ditunggu dengan era society 5.0, penelitian ini menjelaskan tantangan perbahan zaman tersebut bagi dunia pendidikan Islam diantaranya adalah aqidah dan akhlak yang harus disiapkan memasuki dalam era baru itu. Dua hal itu sebagai pedoman yang perlu disiapkan terutama bagi anak-anak sebagai pelanjut generasi guna membentengi diri mereka dari arus globalisasi yang tidak sesuai dengan ajaran Islam. Penelitian ini merupakan penelitian kualitatif dengan pendekatan normative etika moral dan menggunakan sumber-sumber sekunder seperti buku, jurnal, koran dan dokumen lainnya yang diyakini keabsahannya. Analisis data mengguanakan analisis deskriptif hingga sampai pada kesimpulan-kesimpulan yang memadai. Penelitian ini menemukan bahwa pendidikan Islam dinilai mampu untuk beradaptasi dengan era baru society 5.0 dengan mengedepankan cara berfikir kritis dan inovatif. Selanjutnya, pendidikan Islam harus menjamin tersedianya sumberdaya manusia yang handal dan kompeten guna penguatan aqidah dan akhlak murid- murid terutama guru dan tenaga kependidikan.